New Methodology for Non-destructive Identification of Body Fluid for Forensic Purposes - Eugenio; Francesco Mercante; Teresa Di Sarno Giusto (Arab Journal of Forensic Sciences & Forensic Medicine)
The purpose of this research study was to test and subsequently validate a method based on the identification of biological fluids by nondestructive analysis, attributing phenotypic characteristics to biological stains. Specifically, a new methodology for non-destructive forensic histological analysis using Alternative Light Source 450 nm + orange filters was developed and validated - also testing its analytical efficiency and inherent degree of probabilistic error. The validation process has been carried out through the creation of a standard database of known samples, in which were included blood-stains, semen stains, saliva stains and urine stains. Histological profiling with the observation of given parameters was included in the study such as fluorescence/absorbance, stain’s shape, intensity of the signal, concentration of the signal etc. 160 reference samples were produced, which were used as a comparison method for subsequent histological profiling activities. Through a method validation procedure developed on four different tests of the technically investigated samples, specific useful ranges were identified for histological-forensic diagnosis of the biological stains, both known in the reference sample and unknown samples. Careful observation of the biological traces revealed several phenotypic characteristics, through which the study took shape. In conclusion, this experimental work made it possible to design and validate a new methodology for histological-forensic diagnosis through a non-destructive analytical methodology, which is particularly useful in the forensic field. Through this study is it possible to identify the histology of stains founded on the findings with a non-destructive analysis; furthermore it has to been specified that, according to the data obtained, it is possible to identify correctly the histological composition of the blood-stains but the histological identification of stains from semen, saliva and urine is still probabilistics.